2020
DOI: 10.1021/acschembio.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Biosynthetic Assembly of Alpiniamide by a Hybrid cis/trans-AT PKS-NRPS

Abstract: Alpiniamide A is a linear polyketide produced by Streptomyces endophytic bacteria. Despite its relatively simple chemical structure suggestive of a linear assembly line biosynthetic construction involving a hybrid polyketide synthase-nonribosomal peptide synthetase enzymatic protein machine, we report an unexpected nonlinear synthesis of this bacterial natural product. Using a combination of genomics, heterologous expression, mutagenesis, isotope-labeling, and chain terminator experiments, we propose that alpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…We then cloned the epn/tmc BGC of BRA-346 using the transformation-associated recombination (TAR) approach ( Zhang et al, 2019 ; Sigrist et al, 2020 ), inserting the target BGC under the control of a strong promoter into a S. coelicolor M1146 “antibiotic null” host organism ( Gomez-Escribano and Bibb, 2011 ). The heterologous organism S. coelicolor M1446- epn/tmc was cultured in A1 medium and its metabolites were analyzed in parallel with the wild-type BRA-346 and the host organism Streptomyces coelicolor M1446 ( Figure 5A ; Supplementary Figure S12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then cloned the epn/tmc BGC of BRA-346 using the transformation-associated recombination (TAR) approach ( Zhang et al, 2019 ; Sigrist et al, 2020 ), inserting the target BGC under the control of a strong promoter into a S. coelicolor M1146 “antibiotic null” host organism ( Gomez-Escribano and Bibb, 2011 ). The heterologous organism S. coelicolor M1446- epn/tmc was cultured in A1 medium and its metabolites were analyzed in parallel with the wild-type BRA-346 and the host organism Streptomyces coelicolor M1446 ( Figure 5A ; Supplementary Figure S12 ).…”
Section: Resultsmentioning
confidence: 99%
“…The epn/tmc BGC was cloned by PCR-based transformation-associated recombination (TAR) method, as described previously ( Zhang et al, 2019 ; Sigrist et al, 2020 ), with minor modifications as detailed in the Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…This antibiotic has an unexpected nonlinear synthesis that involves a hybrid polyketide synthase-nonribosomal peptide synthetase. It is assembled in two halves and is then ligated into the mature molecule [ 37 , 38 ]. Another compound produced by one of the isolated strains is the polyketide alteramide A.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent genome-mining studies revealed Streptomyces sp. CBMAI 2042, an endophytic strain isolated from Citrus sinensis branches, to be a promising source of secondary metabolites ( Sigrist, Paulo et al, 2020;Sigrist, Luhavaya et al, 2020;Paulo, Sigrist, Angolini, Eberlin et al, 2019). Additionally, biotransformation experiments using whole cells revealed the capability of the strain to promote epoxide hydrolysis (unpublished results).…”
Section: Introductionmentioning
confidence: 99%